Examining enablers of vaccine hesitancy toward routine childhood and adolescent vaccination in Malawi - Gbadebo Collins Adeyanju; Cornelia Betsch; Abdu A. Adamu; Khadijah Sanusi Gumbi; Michael G. Head; Aristide Aplogan; Haoua Tall; Tene-Alima Essoh (BMC, 2022)
Abstract Background The contribution of vaccination to global public health and community wellbeing has been described as one of the greatest success stories of modern medicine. However, 13.5 million children still miss at least one of their routine vaccinations, and this contributes to about 1.5 million deaths from vaccine-preventable diseases. One of the contributing factors has been associated with vaccine hesitancy. Vaccine hesitancy is the delay or refusal of vaccines despite their availability. The study explored factors from multiple perspectives that influence hesitancy among caregivers of children and adolescent girls eligible for childhood routine immunisation and the Human Papillomavirus vaccine in Malawi. Methods The methodology used was qualitative such as key informant interviews and focus-group discussion. Information was obtained from caregivers, community and religious leaders, leaders of civil society groups, teachers in schools where Human Papillomavirus vaccine were piloted, healthcare workers, national and district-level officials of the expanded program on immunisation. There were 25 key informant interviews and two focus-group discussions, with 13 participants. The study was conducted between April to May 2020. The Interviews and discussions were audio-recorded, transcribed, and analysed using a thematic content approach. Results Most vaccine-hesitancy drivers for routine immunisation were also relevant for the HPV vaccine. The drivers included inadequate awareness of the vaccination schedule, rumours and conspiracy theories exacerbated by religious beliefs, low literacy levels of caregivers, distance and transport to the vaccination clinic, gender role and a disconnect between community healthcare workers and community leaders. Conclusions The study demonstrated that a network of factors determines vaccine hesitancy for childhood Routine Immunisation and Human Papillomavirus, and some of them are interrelated with one another. This has implications both for current levels of vaccine acceptance and the introduction of any new vaccine, such as those against Malaria, HIV/AIDS, HPV or COVID-19 (coronavirus disease 2019). Therefore, strategies developed to address vaccine hesitancy must be multi-component and wide-ranging.